Kesenjangan sosial ekonomi pasca pandemi covid-19 dan upaya pemulihan di kabupaten Banyuwangi - Purnomo, Teguh (Universitas Negeri Surabaya, 2025)
This study aims to analyze the post-pandemic socio-economic gap and recovery efforts in Banyuwangi Regency. Using a literature review approach and bibliometric analysis with VOS Viewer, the research identifies the factors contributing to the socio-economic gap in Banyuwangi, as well as the strategies implemented for recovery. The analysis reveals that unequal access to technology, education, and economic resources is a major cause of the gap. On the other hand, recovery efforts focused on developing MSMEs, tourism, rebranding local products such as Banyuwangi batik, and the Banyuwangi Rebound program have played a significant role in reducing the negative impacts of the pandemic. These findings provide valuable insights for the government and economic actors in designing more inclusive policies based on local community empowerment for sustainable recovery.